COVID-19 restrictions in the US: wage vulnerability by education, race and gender - Gambau, B; Palomino Quintana, JC; Rodríguez, JG; Sebastian, R (Taylor and Francis, 2021)
We study economic vulnerability to the stay-at-home orders and social distancing measures imposed to prevent COVID-19 contagion in the US by education, race, gender, and state. Under 2 months of lockdown plus 10 months of partial functioning we find that, without compensating policies, wage inequality and poverty would increase in the US for all social groups and states. We estimate a national potential increase in inequality of 4.1 Gini points and of 9.7 percentage points for poverty, with uneven increases by race, gender, and education. The restrictions imposed to curb the pandemic produce a double process of divergence: both inequality within and between social groups increase, with education accounting for the largest part of the rise in inequality between groups. Education level differences also impact wage poverty risk more than differences by race or gender, making the low-educated the most vulnerable group, while workers with higher education of any race and gender are less exposed. When measuring the potential percentile rank change, most women with secondary education or higher move up, while most men without higher education suffer downward mobility. Our findings can inform public policy aiming to address the disparities in vulnerability to pandemic-related shocks across different socioeconomic groups.